2015
DOI: 10.3390/ma8095269
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages, Foreign Body Giant Cells and Their Response to Implantable Biomaterials

Abstract: All biomaterials, when implanted in vivo, elicit cellular and tissue responses. These responses include the inflammatory and wound healing responses, foreign body reactions, and fibrous encapsulation of the implanted materials. Macrophages are myeloid immune cells that are tactically situated throughout the tissues, where they ingest and degrade dead cells and foreign materials in addition to orchestrating inflammatory processes. Macrophages and their fused morphologic variants, the multinucleated giant cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
458
2
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 540 publications
(490 citation statements)
references
References 219 publications
(256 reference statements)
10
458
2
20
Order By: Relevance
“…135 In particular, macrophages play a critical role in the inflammation process by secreting pro-inflammatory cytokines that are heavily involved in tissue repair and foreign body reactions. 136 Indeed, the activation of macrophage-like (Type A) synoviocytes is critically implicated in the pathology and progression of both osteoarthritis and rheumatoid arthritis.…”
Section: Resultsmentioning
confidence: 99%
“…135 In particular, macrophages play a critical role in the inflammation process by secreting pro-inflammatory cytokines that are heavily involved in tissue repair and foreign body reactions. 136 Indeed, the activation of macrophage-like (Type A) synoviocytes is critically implicated in the pathology and progression of both osteoarthritis and rheumatoid arthritis.…”
Section: Resultsmentioning
confidence: 99%
“…This capsule represents the end stage of a repair process, which begins when plasma proteins contact and adhere to the material during implantation. Various proteins act as chemotactic factors for the infiltration of neutrophils and macrophages [98]. The types of cells present or absent from the interface characterize the nature of the reaction.…”
Section: Discussionmentioning
confidence: 99%
“…4k), infiltration of chronic cell (Table 1) and the capsule formation. The size, irregular shape, and the lack of solubility of material may be the causes of the formation of giant cells granulomas 58) . In this work, it was shown that ZnO and Gt powders have an effi cient antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%